Enterococcus faecalis persistence in pediatric patients treated with antibiotic prophylaxis for recurrent urinary tract infections. (August 2018) - Whiteside, Samantha A; Dave, Sumit; Seney, Shannon L; Wang, Peter; Reid, Gregor; Burton, Jeremy P
Aim: Enterococcus faecalis is one of the most common causes of recurrent urinary tract infection (RUTI), yet enterococcal pathogenesis is poorly understood. Our aims were to identify the prevalence of enterococci in RUTI patients and characterize the enterococcal response to nitrofurantoin and trimethoprim-sulfamethoxazole.Materials & methods: We studied pediatric patients receiving antibiotic prophylaxis and those only under clinical observation for 12 months (n = 39). We then assessed the response of uropathogenic E. faecalis to nitrofurantoin and trimethoprim–sulfamethoxazole.Results: Enterococci were isolated from almost half of patients and exposure of Enterococcus to nitrofurantoin increased virulence properties; this did not correlate with increased expression of virulence factors.Conclusion: Our results demonstrate that antibiotic prophylaxis may not be suitable for treatment of enterococcal RUTI (NCT02357758).